2015
DOI: 10.15640/ijhs.v3n3a6
|View full text |Cite
|
Sign up to set email alerts
|

"The IMPACT of New Media on Child Socialization" Appliedre Search on Basic Education Schools in Muscat Governorate –Sultanate of Oman

Abstract: The problem of the current research represents an attempt to identify the positive and negative effects of New Media on the socialization process of the Omani children through a number of core dimensions: language, identity, values and religious practices. Also the research included some main concepts such as: new media, Internet, social networks and socialization as well as some sub-concepts such as: language, identity, values and religious practices. The research aims to identify the impact of New Media on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Being an interval scale, a three-point Likert response scale (from low influence through medium influence to high influence) was used to choose the most appropriate response. The Likert scale was chosen as the children prefer to respond to the scale and considered the scale to be easiest to fill out (Laerhoven et al , 2004; Royeen, 1985). The data collection period lasted three months from September-November 2017–2018.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Being an interval scale, a three-point Likert response scale (from low influence through medium influence to high influence) was used to choose the most appropriate response. The Likert scale was chosen as the children prefer to respond to the scale and considered the scale to be easiest to fill out (Laerhoven et al , 2004; Royeen, 1985). The data collection period lasted three months from September-November 2017–2018.…”
Section: Methodsmentioning
confidence: 99%
“…Social media is getting popular with young children and influences purchase intention, as well as influences product involvement in family decision-making (Chellasamy and Nair, 2020). Children are affected by new forms of media such as satellite channels and online social networks in Oman (Saleh and El-Rawas, 2015).…”
Section: Children's Consumer Socializationmentioning
confidence: 99%
“…The fact that children pay attention to media and like watching commercials should bode well for advertisers aiming at this expanding market segment in Saudi Arabia (Yavas and Abdul-Gader, 1993). In one of a very interesting study in Oman, researchers found that young children are also get affected by the new media such as satellite channels and social networks (Saleh and El-Rawas, 2015).…”
Section: Gulf Cooperation Council Countriesmentioning
confidence: 99%
“…For example, programs such as Word, PowerPoint, Moodle, and PDF were "heavily" used, with a relatively average usage of more than 80%. Moreover, 1 To determine the levels of relative strength or relative averages that will result from the analysis of field data for the current research, the researchers will use the following criterion: weak (less than 50%), acceptable (from 50% to less than 65%), strong (from 65% to less than 80%), and very strong (more than 80%) [19]. some programs and applications, such as Zoom, Excel, SPSS, and Prezi, were moderately used, where the relative average of use was less than 65%.…”
Section: Ict Systems Programs and Applicationsmentioning
confidence: 99%